Health-Related Fitness of Adolescent Boys with Type 1 Diabetes Mellitus After Recreational Football Exercise with Caloric Control (The Review of Diabetic Studies, 2023)
Objective: The current study investigated the influence of recreational football exercise integrated with caloric control on the health-related fitness in adolescent males with type 1 diabetes mellitus (T1DM). Methods: We divided the participants into four distinct groups. The first group played football and followed a diet plan (FDG), while the second group played only football (FG), meanwhile, the third group had only a diet plan (DG), and the fourth group represented the control group (CG). Every group consisted of 10 male participants. The FDG and FG played twice weekly 90 minutes of football for 12 weeks. Body mass, body mass index (BMI), abdominal endurance, explosive strength, handgrip strength, trunk flexibility, and estimated VO2 max were measured before and after the 12 weeks. Changes in these variables were considered significant if p ≤ 0.050 and the value of effect size (ES) ≤ 42 % or ES ≥ 58 %. Results: Both the DG and FDG experienced a significant decrease in both body mass and BMI. Moreover, only the FDG experienced significant increases in all muscular fitness parameters and an increase in estimated VO2 max. The FG experienced significant increases in explosive strength and handgrip strength. Conclusion: An intervention of 12 weeks of integrated football with caloric control offers the highest improvements in musculoskeletal and cardiovascular fitness in adolescent boys with T1DM, thus improving their overall healthrelated fitness.